Decreasing trends in overweight and obesity among an Australian population of preschool children. - Nichols, MS; Silva-Sanigorski, A; Cleary, J; Goldfeld, SR; Colahan, A; Swinburn, B (2011)
BACKGROUND: After several decades of increasing prevalence, recent evidence suggests a levelling of obesity rates in some groups, although little is known about trends in children under 5 years of age. AIM: To investigate the prevalence, trends and sociodemographic correlates of overweight and obesity in Australian preschool children between 1999 and 2007. METHODS: Child anthropometric and demographic data were extracted from records of routine maternal and child health consultations for children aged 2 and 3.5 years in the Australian state of Victoria. Data were analysed for prevalence of overweight and obesity (according to International Obesity Task Force definitions), trends in prevalence from 1999 to 2007 and sociodemographic correlates of prevalence and trends. RESULTS: Complete data were available for 129,266 2-year-old children and 96,164 3.5-year-old children from 41 local government areas across Victoria. Combined prevalence of overweight and obesity decreased significantly between 1999 and 2007 in 3.5-year-old children (by 3.1% points from 18.5 to 15.4%) and in 2-year-old children (1.1% point decrease from 13.5 to 12.4%). There was no accompanying increase in rates of underweight. Decreases were more pronounced in areas of lower socioeconomic status (SES). Prevalence of both overweight and obesity was consistently higher across time in the older group of children, in the lowest quartile of SES and among girls. CONCLUSIONS: Prevalence of overweight and obesity in preschool children in Victoria has decreased significantly between 1999 and 2007, whereas socioeconomic disparities have narrowed. Further research is needed to understand the reasons for the decreasing prevalence, and to better evaluate existing and emerging health promotion initiatives. Such evidence will be important to build on the findings of this study and to transfer lessons learnt to other population groups.